2020
DOI: 10.1590/0001-3765202020190155
|View full text |Cite
|
Sign up to set email alerts
|

Season effects on the suckling behavior of piglets

Abstract: The suckling behavior of piglets was evaluated in summer and winter, using 21 sows of the same genetic line. Data were collected in July (winter) and in January (summer). The experimental design was a randomized complete block (age of piglets) in a 2x2 factorial scheme, with season of the year (winter and summer) and shift (day, from 06 h to 1h:59min and night from 18h to 05h:59min) as factors. The behavioral variables analyzed were number, interval, and frequency of suckling. The behaviors were monitored on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Nevertheless, in the study by Weary et al [ 34 ], nursing frequency declined slightly during the course of lactation for sows in conventional pens as well. This was confirmed by Moreira et al [ 35 ], who found a decrease in nursing frequency in early lactation from day 7 to 15 after birth in crated sows. In the aforementioned study, the nursing interval increased from 30 to 34.9 min, whereas in the current study, the interval initially decreased from 47.4 to 43.7 min in the second week.…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, in the study by Weary et al [ 34 ], nursing frequency declined slightly during the course of lactation for sows in conventional pens as well. This was confirmed by Moreira et al [ 35 ], who found a decrease in nursing frequency in early lactation from day 7 to 15 after birth in crated sows. In the aforementioned study, the nursing interval increased from 30 to 34.9 min, whereas in the current study, the interval initially decreased from 47.4 to 43.7 min in the second week.…”
Section: Discussionsupporting
confidence: 70%
“…The data that did not present normal distribution were normalized by the PROC RANK in the SAS (9.3) software [18]. The Kruskal-Wallis test was used to compare nonnormalized data at a 5% probability.…”
Section: Discussionmentioning
confidence: 99%
“…number, interval, and duration of sucklings were evaluated when 50% + 1 the litter began suckling, and ended when more than half of the litter left sented inactive behavior, as recommended by Moreira et al [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, temperature plays a key role in animal activity, and animals become more lethargic in warmer environments. Moreira et al [25] observed the effect of temperature on the suckling behavior of piglets and found that the duration of the suckling behavior was shorter in summer than in winter, and the piglets suckled more often during the night. This strategy and others such as adapting their lying or eating behaviors are used by pigs to counterbalance the effects of being out of their thermoneutral zone.…”
Section: Series Decomposition and Analysis Of The Trend And Seasonality Componentsmentioning
confidence: 99%